ANALISIS PENGARUH PENGUMUMAN BOND RATING TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN (Studi Kasus Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2008 – 2011) - Indrago Indrago; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2014)
This study aims to analyze the effect of bond rating on stock price and stock trading volume on companies listed in Indonesia Stock Exchange from 2008 to 2011.The study used secondary data with samples size of 136 companiesconducted by purposive sampling. The data used are daily closing stock price and daily trading volume. Hypothesis testing is using paired samples T – test.The tools which is used with SPSS 19.0 version.The results indicates that there are no significant effectof bond rating on stock price and volume trading before, during and after the announcement.Keywords: Bond Rating, Stock Price, Volume Trading